Recovery of fatty acids by immobilized solvent extraction - 333347 Lau, Isaac; Hayward, Gordon
The use of silicone rubber tubes swollen with solutions of TOPO (trioctyl phospine oxide) in kerosene as membranes for the recovery of fatty acids from anaerobic digesters was investigated. The flux of acetic and propionic acids was found to increase with the concentration of TOPO when the concentrationwas low. At very high TOPO concentration, the flux decreased indicating the existance of an optimum TOPO concentration. The relationship between the flux and concentration of unionized propionic acid did not agree with that expected for pure diffusion. This was due to the reversible reaction between TOPO and propionic acid in the membrane. The flux of propionic acid was measured as a function of time for new membranes and for membranes removed from storage. Rather long times, 70 to 300 hours, were required to achieve steady acid fluxes. This time was required to fully developed the concentration profiles within the membranes.